Effect of swift heavy ion irradiation on the migration behaviour of Xenon implanted in spark plasma sintered titanium nitride and titanium carbide. - Hlatshwayo, Thulani Thokozani (University of Pretoria, 2021)
Thesis (PhD (Physics))--University of Pretoria, 2021.